Exploring the Effects of Critical Pedagogy-Based Teaching Materials on the Adoption of a Critical Stance Towards Social Issues (2022)
ABSTRACT: This case study aimed at exploring the effects EFL Critical Pedagogy-based materials had on sixth graders’ adoption of a critical stance toward social issues, specifically, stereotypes related to people’s place of origin. The thirty-nine students who participated in this study belong to a 6°C class of I.E.E. Normal Superior María Auxiliadora, a public school in Copacabana, Antioquia. Actions included were describing the context, choosing the topic according to the curriculum, designing and implementing materials supported by the Problem Posing framework, and preparing students in terms of the linguistic elements required. Findings suggest that the implementation of such materials helped students both improve their linguistic proficiency, as well as be able to realize the following three principles of Critical Pedagogy: a) problematizing situations, b) examining multiple perspectives in situations c) proposing actions to challenge the status quo in situations.